A Novel Approach to Optimize Cognitive Radio Network Utilization using Cascading Technique - H Venkatesh Kumar; M.N. Giriprsad (Universitas Ahmad Dahlan, 2015)
The cognitive network suffers from scarcity of channels. The Unlicensed users (UU) borrow channels from the licensed users (LU). But when the LUs want them, the UUs have to stop their transmission and handle the channel back to the LUs. This results in delay in transmission of data by UUs. We propsed an algorithm mostly focusing to meet the delay,by using a data cascading technique where the data of the UUs are stored in the intermediate nodes so that even if the transmission is interrupted, the data is not lost. The experimental results show that proposed system is better than other existing systems.